2020
DOI: 10.1177/1473225420924123
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Measure Standard Costs of Juvenile Justice Systems: The Example of Italy

Abstract: This study proposes a standard costs method to evaluate the total direct costs of a juvenile justice system and applies it to the Italian case. The proposed cost-analysis method based on standard costs by offense-related groups illustrates how it can be implemented for improving the quality of management and cost monitoring. An illustrative cost-benefit analysis of the costs of juvenile justice in Italy shows that investments in rehabilitation programs are highly attractive even during a period of economic cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…62 Gili (2013): 99, reports that the daily average cost of each social service worker of the USSM amounted to 222.39 euros in 2013. More recently, Ciappi et al (2022): 32, affirm that for court hearings activities the costs vary between €400 and €600: 'there is a minimum of two to a maximum of five public hearings per person (initial, pretrial, and verification) because all care packages involve the juvenile court. In each hearing, operators are involved for between 4 and 6 hours at €32 per hour'.…”
Section: Fragile Barriers For Privacy?mentioning
confidence: 99%
“…62 Gili (2013): 99, reports that the daily average cost of each social service worker of the USSM amounted to 222.39 euros in 2013. More recently, Ciappi et al (2022): 32, affirm that for court hearings activities the costs vary between €400 and €600: 'there is a minimum of two to a maximum of five public hearings per person (initial, pretrial, and verification) because all care packages involve the juvenile court. In each hearing, operators are involved for between 4 and 6 hours at €32 per hour'.…”
Section: Fragile Barriers For Privacy?mentioning
confidence: 99%
“…A type of case mix adjustment might be applied to measure the productivity of other public services, but obviously requires sufficient and robust data to support such an approach. For example, Ciappi et al (2015) suggested that a similar approach to DRGs could be applied to the justice system in Italy. A standard cost could be calculated for a specific type of offender.…”
mentioning
confidence: 99%